STUDI LITERATUR: PENGARUH KURANG TIDUR TERHADAP KERUSAKAN DNA DAN KESEHATAN SEL. - Khairiyah Ariqah; Siti Ajilah Syarwan Chaniago; Najwa Syifa Nasution; Maria Oktavia Sitorus; Ida Duma Riris; Diva Aulia Ananda; Daniel Ritonga (STKIP Subang, 2026)
Sleep deprivation is an increasingly common problem due to changes in modern lifestyles and can have negative impacts on health. One of the most significant biological consequences is the increase in oxidative stress, which may lead to DNA damage and impaired cellular function. This study aims to examine the effects of sleep deprivation on DNA damage and cellular health based on findings from various published studies. The method used was a qualitative literature review. Data were collected from national and international scientific articles discussing the relationship between sleep deprivation, oxidative stress, DNA damage, and cellular health. The collected data were analyzed descriptively to identify the relationships among these variables. The review findings indicate that sleep deprivation increases the production of Reactive Oxygen Species (ROS), which triggers oxidative stress and causes DNA damage. Furthermore, sleep deprivation may inhibit DNA repair mechanisms, alter gene regulation, and increase the accumulation of genetic damage within cells. Persistent DNA damage can induce cellular aging, apoptosis, and increase the risk of various chronic diseases. Therefore, adequate sleep quality and duration are essential for maintaining DNA stability and cellular health.